PERANCANGAN READY – TO – WEAR DELUXE BERKONSEP SUSTAINABLE FASHION UNTUK BRAND ALLEGRA JANE - Janet Teowarang (Universitas Ciputra Surabaya, 2019)
This designed collection is made to promote Sustainable Fashion, which is of particular concern with the abundance of waste in the fashion industry, especially in Indonesia. Domestically, there are still many consumers who buy fast fashion products and have not extensively used environmentally friendly products made in Indonesia. Seeing the importance of local fashion brands lifting the concept of Sustainable Fashion by preserving Indonesian art and culture, ALLEGRA JANE a fashion brand made the designs in the form of Ready – to – Wear collection or also called ready – made clothes using ATBM woven fabric and Pasuruan Batik with natural coloring. The Pasuruan Batik Motif selected for this collection is called Tansah Kelingan, which is the motif of chrysanthemum flowers and tuberose flowers. The other motif is Sumebyar Ing Kalen, which is a rose motif and tuberose flowers motif, both of these Batik designs are equipped with detailed technique of hand written Batik of sprinkles. The design collection is inspired by Autumn Winter 2019 - 2020 color and fashion trends. The designs of this collection have straight silhouettes and tailoring structures that can be easily combined with outers, tops and bottoms worn as semi-casual wear or semi-formal wear.